The Irish regiments in the Great War : discipline and morale - Bowman, Timothy (Manchester University Press ; Distributed exclusively in the USA by Palgrave, 2003)
A comprehensive study of discipline and morale in the British army during the Great War, using the Irish regiments as a case study. The book suggests that, while minor breaches of discipline did occur in the Irish regiments, executions took place out of the need to restore military discipline.
Keywords: Great Britain. -- Army -- Irish regiments -- History.; Grande-Bretagne. -- Army -- Régiments irlandais -- Histoire.; Great Britain. -- Army; World War, 1914-1918 -- Regimental histories -- Great Britain.; World War, 1914-1918 -- Regimental histories -- Ireland.; Guerre mondiale, 1914-1918 -- Histoire des unités -- Grande-Bretagne.; Guerre mondiale, 1914-1918 -- Histoire des unités -- Irlande.; Humanities.; History.; Military history.; First World War.; HISTORY -- Military -- World War I.; HISTORY -- Europe -- Great Britain.; Regimental histories; Ireland; Great Britain; Weltkrieg -- 1914-1918; Großbritannien; Regiment; Regimenten.; Moraal.; Discipline.; Eerste Wereldoorlog.; Guerre mondiale (1914-1918) -- Grande-Bretagne.; Guerre mondiale (1914-1918) -- Participation irlandaise.; Guerre mondiale (1914-1918) -- Histoire des unités -- Irlande.; Guerre mondiale (1914-1918) -- Histoire des unités -- Grande-Bretagne.; Iren.; 1914-1918; Multi-User.; Electronic books.; History